Environmental issues regarding CO2 and recent strategies for alternative fuels through photocatalytic reduction with titania-based materials. Issue 4 (December 2016) - Akhter, Parveen; Farkhondehfal, M. Amin; Hernández, Simelys; Hussain, Murid; Fina, Alberto; Saracco, Guido; Khan, Asad U.; Russo, Nunzio
Graphical abstract: Highlights: Environmental issues regarding CO2 and recent strategies for alternative fuels. CO2 utilization technologies for renewable fuel formation. Photocatalytic reduction of CO2 with titania-based materials. Abstract: Carbon dioxide (CO2 ) is considered one of the main contributors to the greenhouse effect and is currently a key challenge throughout the world. Therefore, the CO2 complications associated with the environment have in particular been focused on in this review, and various strategies regarding CO2 mitigation, or the utilization of different technologies to produce renewable fuels or useful chemicals to overcome the energy crisis, have been considered together with the recent developments in the photocatalytic reduction of CO2 by means of different titania photocatalysts to produce various energy-bearing products. The problems, progress and future prospects regarding CO2 utilization are presented. This present review indicates that the devolvement of efficient active photocatalysts for this technology is still under way and that better efficiency of the desired products could be accomplished. It is also shown that this technique is still at an embryonic stage, due to a lack of proficiency, and that the yield discrimination is very low. It can therefore be concluded that further research efforts are needed to boost this process towards commercialization in the near future.